KEHIDUPAN PEREMPUAN PENAMBANG PASIR GUNUNG DI KELURAHAN TOBIMEITA KECAMATAN NAMBO KOTA KENDARI. - Hermawan, La Ode; Hartini, Hartini (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
The aim of this research is to understand the lives of mountain sand miners as they carry out their duties in factories and domestic areas. This research reads the data with Ralph Linton's thinking, status, and role theory. Data col lection techniques in this research are observation, in-depth interviews, and documentation. The results of this research show that women who work in public areas in mountain sand mining feel that their family's needs are not sufficiently met by relying solely on income from their husbands and single parents, who have to support their families. So this dual role is carried out at the same time and is balanced between the domestic role and the public role. Through Ralph Linton's thinking, status personality is a set of typical personalities that correspond to a person's status in everyday life. The status in question is employment. Women who work in mountain sand mining in Tobimeita Village do not only have typical jobs, but they also have additional status that is appropriate to the situation. In the morning before work, they act as wives and mothers, while when they work, they act as women breadwinners.